Effects of Microlectures on Nursing Students' Understanding of Key Medication Administration Concepts: A Quasi-Experimental Design. Issue 2 (4th March 2023) - Yu, I-Chen; Fang, Ji-Tseng
Abstract : Background: Microlectures comprise short audio or video presentations designed to provide a concise explanation of key concepts or topics. Purpose: The study aimed to develop a microlecture module for a nursing course in medication administration and test whether it could improve learning. Methods: The study had a quasi-experimental design. Four classes of sophomore nursing students were divided into the treatment (n = 109) and control groups (n = 84). Pretests, posttests, integrated examinations, and simulated experiences were employed. Analysis of covariance were used to analyze the students' pretest, posttest, and integrated examination performances. Results: The treatment group performed better than the control group. Conclusions: This study provides nursing educators with a different approach to traditional teaching and sheds light on how to design a microlecture.